Bridging the gap between hyperspectral imaging and crop breeding: soybean yield prediction and lodging classification with prototype contrastive learning - Guangyao Sun; Yong Zhang; Lei Wang; Longyu Zhou; Shuaipeng Fei; Shiteng Han; Shunfu Xiao; Yingpu Che; Long Yan; Yun Xu; Yinghui Li; Lijuan Qiu; et al. (Computers and Electronics in Agriculture, 2025)

The roles of different Fe-based materials in alleviating the stress of Cr(VI) on anammox activity: Performance and mechanism - Beichen Zhang; Jingshu Wang; Shiteng Feng; Jinhui Jeanne Huang; Xiaoyu Han (Chemical Engineering Journal, 2023)

Innovation Concept Model and Prototype Validation of Robotic Fish with a Spatial Oscillating Rigid Caudal Fin - Shuyan Wang; Yu Han; Shiteng Mao (Journal of Marine Science and Engineering, 2021)
Inspired by carangiform fish with a high-aspect ratio of the caudal fin’s up-down swing, but also by dolphins with a similar caudal fin’s left-right swing, a robotic fish with a spatial oscillating rigid caudal fin is implemented to optimize propulsion and maneuverability, whose orientation could be transformed to any position of a taper domain. First, three steering-engines were adopted to make the conceptual prototype, and an experimental apparatus for measuring thrust, lift forces, lateral forces and torque was developed. Then, three comparison experiments, respectively corresponding to the three modes of cruise, diving and maneuvering in random space, were conducted to imitate bionic fish’s hydrodynamics. The comparison results of the experiments proved that propelling and maneuvering in any direction could be realized through changing the orientation of the spatial oscillating rigid caudal fin.

Expression of CagL from Helicobacter pylori and Preliminary Study of its Biological Function - Hua Wang; Shiteng Huang; Jianzhong Zhao; Jun Han; Xianwei Guan; Shihe Shao (Indian Journal of Microbiology, 2013)

Characterization of peptidoglycan hydrolase in Cag pathogenicity island of Helicobacter pylori - Qiao Zhong; Shihe Shao; Runhong Mu; Hua Wang; Shiteng Huang; Jun Han; He Huang; Shuwei Tian (Molecular Biology Reports, 2011)